Reproductive aspects of naleh fish (Barbonymus sp.): A native species from Nagan river, Aceh Province, Indonesia - Deni Efizon; Agung S. Batubara; Zainal A. Muchlisin; Roza Elvyra; Syamsul Rizal; Mohd N. Siti-Azizah (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Efizon D, Batubara AS, Muchlisin ZA, Elvyra R, Rizal S, Siti-azizah MM. 2021. Reproductive aspects of naleh fish (Barbonymus sp.): A native species from Nagan river, Aceh Province, Indonesia. Biodiversitas 22: 2682-2690. Naleh fish (Barbonymus sp.) is a native species in Indonesia and reproductive biology is key information to planning a better conservation strategy for this species. Hence, the present study aimed to examine the spawning season, sex ratio, and fecundity of the naleh fish harvested from Nagan Raya District, Aceh Province, Indonesia. Sampling was conducted from January to December 2016 at three sampling locations that were determined purposively based on the recommendations of local fishermen. The fish samples were caught using casting nets and gillnets at two-week intervals. A total of 761 fish samples, comprising 135 females and 626 males, with males predominating at a ratio of 1:4.6 (female: male). The gonadosomatic index (GSI) average of the females ranged from 0.58% to 4.28%, while 1.24% to 4.18% for males. The male fish first matured at 73 mm, whereas the female reached maturity at a size of 85 mm. The total fecundity ranged from 656-5725 eggs with an average of 2663.2 eggs, whereas the relative fecundity from 35.69-254.65 eggs gram-1 body weight with an average of 136.88 eggs gram-1 body weight. Our finding able to demonstrate that reproductive properties of Barbonymus sp. allow us to better estimate their spawning season either females and males, which can be useful for conservation planning and also their fecundity data was important for aquaculture development in the future.